2019
DOI: 10.1097/iop.0000000000001127
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in the American Society of Ophthalmic Plastic and Reconstructive Surgery

Abstract: Women and URMs have increased steadily in ASOPRS, especially in recent years. Similar to the rest of ophthalmology and general medicine, there remain opportunities for ASOPRS to increase diversity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 3 publications
0
18
0
Order By: Relevance
“…Within the American Society of Ophthalmic Plastic and Reconstructive Surgery (ASOPRS), there has been an increase in the percentage of female members from 3.8% in the first decade of the organization (1969–1978) to 45.2% in the fifth decade (2009–2018). 5 Charlson et al 4 also found that women ASOPRS members trended toward achieving full professor rank less often than their male counterparts, although this was not statistically significant. While the number of women ASOPRS members has been studied previously, there have been no studies examining authorship gender trends in oculoplastics journals.…”
mentioning
confidence: 94%
“…Within the American Society of Ophthalmic Plastic and Reconstructive Surgery (ASOPRS), there has been an increase in the percentage of female members from 3.8% in the first decade of the organization (1969–1978) to 45.2% in the fifth decade (2009–2018). 5 Charlson et al 4 also found that women ASOPRS members trended toward achieving full professor rank less often than their male counterparts, although this was not statistically significant. While the number of women ASOPRS members has been studied previously, there have been no studies examining authorship gender trends in oculoplastics journals.…”
mentioning
confidence: 94%
“…Thus, it is encouraging that recent years have brought a heightened awareness of these issues. In some areas, disparities are even starting to diminish [10]. Just remember that progress and shortfall are not mutually exclusive.…”
Section: Prefacementioning
confidence: 99%
“…3 This trend percolates through the various ophthalmologic subspecialties as well, including retina and oculofacial plastic surgery, with only 4.2 and 9.4% of practicing specialists self-identifying as UiM, respectively. 5,6 This lack of representation can diminish access to adequate health care and drive health disparities. 7 Prior literature has shown that UiM physicians are more likely than their non-UiM counterparts to work in predominantly UiM communities, which are also more likely to experience physician shortages and the aforementioned disparities.…”
mentioning
confidence: 99%
“…13 The lack of representation in leadership roles and academic positions impacts patient care as prior research has noted gender to influence patient counseling services, communication styles, and patient satisfaction. 5 In 2020, transgender and gender nonbinary (TGNB) people accounted for about 0.8% of medical school matriculants. 15 Representation of TGNB people in surgery and surgical subspecialties is lacking.…”
mentioning
confidence: 99%